KEEFEKTIFAN PERMAINAN ã‚¹ãƒªãƒ¼ãƒ’ãƒ³ãƒˆã‚²ãƒ¼ãƒ TERHADAP PEMBELAJARAN KOSAKATA BAHASA JEPANG (Penelitian Eksperimen Terhadap Mahasiswa Bahasa Jepang Tingkat I FKIP Universitas Riau) - Habibah, Siti Habibah Siti; Basri, Merri Silvia Basri Silvia; Widiati, Sri Wahyu Widiati Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine whether the game ã‚¹ ãƒª ãƒ¼ ãƒ’ ãƒ³ ãƒˆ ã‚² ãƒ¼ ãƒ  can improve learning outcomes Japanese vocabulary of the Japanese language student level I FKIP University of Riau. In this study the authors used Desain experimental study design with test I and test II. The object of this study is a Japanese student level I FKIP Riau University consisting of 14 samples of the study. Data collection techniques done by providing tests and interviews. Tests were carried out which tests I and II tests to determine the results of student learning Japanese vocabulary when action I (memorizing) and Action II (gameã‚¹ ãƒª ãƒ¼ ãƒ’ ãƒ³ ãƒˆ ã‚² ãƒ¼ ãƒ ). Results of the test of action I and II test results action is processed using statistical test t-test using SPSS to determine how much significance level student learning outcomes when using the game ã‚¹ ãƒª ãƒ¼ ãƒ’ ãƒ³ ãƒˆ ã‚² ãƒ¼ ãƒ .Based on statistical data processing with SPSS, showed a significance of 0.001. This means that the figure of significance obtained is less than 0.05 (0.001 <0.05), the Ha accepted and H0 is rejected, there is a significant difference to the effectiveness of the game ã‚¹ ãƒª ãƒ¼ ãƒ’ ãƒ³ ãƒˆ ã‚² ãƒ¼ ãƒ  on learning the vocabulary of Japanese student level I Prodi Language Education Japan FKIP UR.Keywords: game ã‚¹ ãƒª ãƒ¼ ãƒ’ ãƒ³ ãƒˆ ã‚² ãƒ¼ ãƒ , learning vocabulary